Methylene blue plus light mediates 8-hydroxy 2'-deoxyguanosine formation in DNA preferentially over strand breakage. - Schneider, J E (1990)
Methylene blue (MB) plus light, in the presence of oxygen, mediates formation of 8-hydroxyguanine in DNA. The yield of 8-hydroxyguanine may be as much as from 2 to 4% of the guanines present. The results presented here show that treatment of supercoiled plasmid DNA with methylene blue plus light causes single-stranded nicks. However, single-stranded nicking occurs approximately 17-fold less frequently than does formation of 8-hydroxyguanine. The nicking rate is reduced in the presence of Mg ion but is not prevented by inhibitors of the iron-catalyzed Fenton reaction or by scavengers of hydroxyl free radicals. Extensive exposure of DNA to light in the presence of MB produces no detectable thiobarbital reactive material thus implicating that single strand nicking does not occur by hydroxyl free radical attack on deoxyribose. Formation of 8-hydroxyguanine is apparently not dependent upon intercalative binding of MB to DNA, since it is formed in polydeoxyguanylic acid.